2017
DOI: 10.1111/risa.12807
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Analysis of Countries under Disasters Based on Multisource Data

Abstract: Disasters occur almost daily in the world. Because emergencies frequently have no precedent, are highly uncertain, and can be very destructive, improving a country's resilience is an efficient way to reduce risk. In this article, we collected more than 20,000 historical data points from disasters from 207 countries to enable us to calculate the severity of disasters and the danger they pose to countries. In addition, 6 primary indices (disaster, personal attribute, infrastructure, economics, education, and occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Such discussion will be in line with current approaches seeking to conceptually deepen the understanding of resilience by introducing more nuanced conceptual structure [33], [34]. But it will also help approaches trying to measure or apply resilience by clarifying the oftentimes overlapping usages of similar terms such as resilience and degree of loss [35].…”
Section: Resilience Immediately After Hazard Impact (Reactive Resiliementioning
confidence: 62%
“…Such discussion will be in line with current approaches seeking to conceptually deepen the understanding of resilience by introducing more nuanced conceptual structure [33], [34]. But it will also help approaches trying to measure or apply resilience by clarifying the oftentimes overlapping usages of similar terms such as resilience and degree of loss [35].…”
Section: Resilience Immediately After Hazard Impact (Reactive Resiliementioning
confidence: 62%
“…A review of catastrophe response found that education is associated with high levels of resilience (Zhang & Huang, 2018). Several publications that detail features of a successful refuge suggest the importance of education or the preservation of knowledge (Baum et al., 2015; Maher & Baum, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We disagree that the island should be “sparsely populated” because larger, denser populations are more resilient and have better capacity to sustain technological flourishing. A 2018 review of catastrophes found that a high population density (with infrastructure, strong economy, and education), focused on a small land area, with a history of exposure to disasters, and a high GDP, was associated with higher levels of resilience (Zhang & Huang, ). This further justifies our general approach, and suggests that further research into the factors that enhance resilience would be useful.…”
Section: Methodsmentioning
confidence: 99%